FROM EXCLUSIVE TO INCLUSIVE-CULTURAL: DECOLONIZATION OF THE CHURCH'S MISSION TO CULTURE AT HKBP PARSAORAN DAME - Hana Masta Pasaribu; Riris Johanna Siagian (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This paper examines the dynamics of the church's decolonization of Batak culture in the context of the HKBP Parsaoran Dame congregation, as a theological effort to free itself from the hegemony of Western theology that historically shaped the colonial mission paradigm. To date, the church's mission has often operated within a dualistic framework that separates the Gospel from custom, faith from culture, and the sacred from the profane, thus creating epistemological tension between Christian faith and local cultural identity. Three theoretical frameworks are used: A. Afaradi's decolonial theology on epistemic liberation from Western domination; Homi K. Bhabha's concept of hybridity and third space, which explains the process of negotiating the meaning of faith in a cultural context; and Robert Sibarani's idea of ​​Dalihan Na Tolu as a source of Batak ethics and spirituality. HKBP Parsaoran Dame is experiencing a mission paradigm shift toward an inclusive, dialogical, and collaborative approach. This process of integration between faith and culture produces a form of religious hybridity that affirms the rootedness of Christian faith in Batak values ​​without losing its universal dimension. Theologically, mission decolonization is understood not merely as the replacement of Western symbols with local elements, but as an epistemic and spiritual liberation that places local culture as the locus theologicus of the space where God is presented and experienced through the language, symbols, and values ​​of society. This research emphasizes that a decolonized church is a church that is culturally rooted yet remains universal in the love of Christ, and makes the values ​​of marsiadapari (mutual cooperation) and marsilupahon (mutual support) the foundation of contextual, liberating, and transformative mission practice. This paper was developed with a qualitative approach through in-depth interviews and participatory observation, this research combines contextual theology and decolonial theory as the basis for analysis.